Analysis of sexually transmitted infections in PrEP users: population assessment in Curitiba, Brazil - Roth, Maria Julia de Moraes Campos; Valderrama, Mariana Rothermel; Acras, Julia Schemberger; Moro, Marjorie Goetz; Lehmkuhl, João Victor Borges; Pazin, Daiane Cristina (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The pre-exposure prophylaxis (PrEP) is a globally recognized pharmacological approach, consisting of a daily dose of antiretroviral drugs used to reduce the contamination rate by the human immunodeficiency virus (HIV). This combined prevention program was first offered by the Brazilian public health system in 2017 and was provided by Testing and Counseling Centers. Objective: To analyze the profile of pre-exposure prophylaxis users seen at Testing and Counseling Centers in Curitiba (state of Paraná, Brazil) and the presence of HIV and other sexually transmitted infections, such as syphilis, hepatitis B and C, in these users. Methods: This is an analytical, cross-sectional study, using database provided by the information system of the Testing and Counseling Center. Results: Users of HIV pre-exposure prophylaxis are mostly young, white, single men, and who are part of the group of men who have sex with other men. It was verified that, even though the HIV pre-exposure prophylaxis plays a major role in HIV prevention, it is paramount to encourage combined prevention, considering there is a significant relationship between the lack of barrier methods and positive results for syphilis. Conclusion: No connection between the use of HIV pre-exposure prophylaxis and increased incidence of sexually transmitted infections was established in the present study